COMMUNICATION: ANALYTICAL UNIT OF TWO SELECTIONS AND TWO CONSTRUCTIONS - Labudović, Boris (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2019)
The paper is inspired by the discursive-analytical strategy and communicational aspects of Niklas Luhmann 's general theory of social systems as well as the conclusions of the Arizona State University Consortium for Strategic Communication. The CSC notes that communication based on the "message influence" model has become dysfunctional and therefore they propose a "pragmatic complexity model” which is primarily drawn from the perspective of new systems presented by Niklas Luhmann. It is no longer a question of "how to construct a more influential message", but "what kind of reality has a particular system that we want to influence constructed for itself." For these reasons, from the broad field of communication science I differentiate the segment related to the study of strategic models for managing public communications with individuals, groups and communities (propaganda, public relations, political marketing). I suggest a distinctive name for this area - Impactology. I then elaborate on the understanding and definition of communication as a symbolic coordination of sense, which, analytically stratified, consists of two selections and two constructions. The alter selects the data and constructs the utterance, and the ego selects the utterance and constructs the understanding (by selecting meaning, contextual interpretation and attributing sense). Thus viewed, every communicational event (commevent) is bidirectional and presents a particular negotiation of sense in which both parties equally participate. This dismisses Berl's SMCR model inspired by Shannon and Weaver as inadequate in the hypercomplex and multi-contextual contemporary world.
Keywords: Luhmann; impactology; communication; function; definition; selection; construction